A unique association of an ancient Indian custom of body roasting and the postpartum psychosis responsible for the occurrence of major burns: A case report and challenges posed by postpartum psychosis in the treatment of burns - Hemant A Saraiya (Wolters Kluwer Medknow Publications, 2019)
Introduction: We report a unique association of an ancient Indian custom of postdelivery mother roasting and postpartum psychosis responsible for the causation of major burns. Materials and Methods: A 20-year-old postpartum female reported with 40% second- and third-degree total body surface area burns. The combination of the ancient Indian custom of mother roasting and postpartum psychosis led to these major burns. The conventional treatment of burns in the form of IV fluids, antibiotics, and dressings with silver sulfadiazine creams was carried out. The psychiatrist was consulted, and the antipsychotic medicines were started for an altered behavior. One month after the burns, she developed deep-vein thrombosis with venous gangrene of the left leg for which she required a below-knee amputation. She required 45 days of hospitalization and six surgical procedures in the form of debridement and split-thickness skin grafting. Problems such as hypotension, noncooperation due to the wild swing in the moods were overcome by proper fluid and electrolyte management, an adjustment in antipsychotic medicines, appropriate postoperative care, and chest physiotherapy. Results: One year of follow-up showed good stable scars. At present, she can perform all domestic as well as labor work on the farm, with the help of a below-knee prosthesis. There is no element of psychotic behavior at present. Conclusion: This case report sheds light on an ancient Indian custom of mother roasting and postpartum psychosis and its dangers in contracting severe burn injuries. Challenges posed by postpartum psychosis in the treatment of burns have been discussed.